دور الصحة الرياضية في الوقاية من الإصابات الرياضية أثناء المسابقات بيالمؤسسات التربوية - شرقاني إبراهيم; بن شريف ياسين (My University, 2023)
تهدف هذه الدراسة إلى تبيان أثر دور الصحة المدرسية في الوقاية من الإصابات الرياضية أثناء المسابقات بالمؤسسات التربوية دراسة ميدانية في ثانوية عمر دهنية بالأغواط، وذلك باستخدام المنهج الوصفي في الجزء النظري والتحليلي في الجزء التطبيقي، والتحقيق أهداف الدراسة تم تصميم استبيان الجمع البيانات وقد وزع على عينة من التلاميذ في ثانوية عمر دهينة ، بلغ عددها (30) استمارة موزعة، تمت معالجتها عن طريق برنامج SPSS توصلت الدراسة إلى مجموعة من النتائج أهمها : يوجد دور الصحة المدرسية لدى تلاميذ أطوار المستوى الثانوي في ثانوية عمر دهنية بالأغواط يوجد تأثير دال إحصائيا دور الصحة المدرسية في الوقاية من الإصابات الرياضية أثناء المسابقات بالمؤسسات التربوية في ثانوية عمر دهنية بالأغواط.
دراسة ميدانية :ثانوية عمر دهينة بولاية الجلفة
This study aims to demonstrate the impact of the role of school health in the Prevention of sports injuries during competitions in educational institutions a field study at Omar dahniya High School in Al-agawat, using the descriptive curriculum in the theoretical and analytical part in the applied part.to achieve the objectives of the study, a questionnaire was designed to collect data and wasdistributed to a sample of the childrin, numbering (30) distributed forms, processed through the SPSS program. The study reached a set of results, the most important of which are There are school Health Centers for secondary-level students at Omar dahniya High School in Al-agawat There is a statistically significant impact on the role of school health in the Prevention of sports injuries during competitions in educational institutions at Omar dahniya Secondary School in Al-agawat.